Analisis Pembelajaran Fisika Materi Dinamika Rotasi: Studi Literatur Publikasi Ilmiah - Siti Maryam Ahlamy; Susilawati Susilawati; Habibah Nurul Padilah; Azam Izzatulhaq (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract This literature research aims to identify rotational dynamics learning problems. The research method used is the System Literature Review (SLR). The results of studying the literature show that a lot of learning research has been carried out on rotational dynamics material. Even though the concept of the material has been conveyed, many students do not understand and fail to apply the concept to solve a problem. This is because the knowledge is still in the form of knowledge and has yet to form a complete knowledge of concepts. Some rotational dynamics learning uses cognitive conflict and analogy. Inappropriate selection of cognitive conflicts and analogies by learners can lead students to make false claims about concepts. Based on the results of the review of the literature study, several recommendations for physics learning models were obtained that could train problem-solving skills with various learning models, scientific approaches, and technological media assistance to support learning activities, especially on rotational dynamics material. Abstrak Penelitian literatur ini bertujuan untuk mengidentifikasi permasalahan pembelajaran dinamika rotasi. Metode penelitian yang digunakan adalah System Literature Review (SLR), Hasil belajar literatur menunjukkan banyak penelitian pembelajaran yang telah dilakukan pada materi dinamika rotasi. Meskipun konsep materi telah disampaikan, banyak siswa yang tidak paham dan gagal dalam menerapkan konsep tersebut untuk menyelesaikan suatu permasalahan. Hal ini disebabkan karena ilmu yang dimiliki masih berupa pengetahuan dan belum membentuk ilmu yang utuh tentang konsep. Beberapa pembelajaran dinamika rotasi menggunakan konflik kognitif dan analogi. Pemilihan konflik kognitif dan analogi yang tidak tepat oleh pembelajar dapat membuat siswa memberikan klaim yang salah pada konsep. Berdasarkan hasil kajian studi literatur didapatkan beberapa rekomendasi model pembelajaran fisika yang dapat melatih keterampilan pemecahan masalah dengan berbagai model pembelajaran, pendekatan saintifik, dan bantuan media teknologi untuk menunjang kegiatan pembelajaran terutama pada materi dinamika rotasi.